Extracorporeal renal replacement therapy and blood purification in critical care. (20th March 2013) - Cowgill, Larry D.; Guillaumin, Julien
Abstract Objective To review indications methods of renal replacement therapies (RRT) and practical considerations for the creation of a RRT program. Data Sources Current human and veterinary literature review with a focus on advanced renal physiology and clinical experience in RRT and acute/chronic kidney diseases. Data Synthesis Renal replacement therapies encompass intermittent hemodialysis, continuous renal replacement therapy as well as some "hybrid" techniques. Each method of RRT has practical and theoretical advantages but currently there is no evidence that one technique is superior to the other. Conclusions RRT is a valuable therapeutic tool for treatment of acute kidney injury and chronic kidney disease. The implementation of an RRT program needs to take into consideration multiple parameters beyond the choice of an RRT platform.